Social Safety Nets: A Possible Pathway to Foster Household Resilience to Emerging Shocks. Evidence from Malawi and Zambia - Sichoongwe, Kiru (Pencerah, 2024)
Social safety nets are a useful weapon in the fight against poverty. The purpose of this study was to examine the types of safety nets that exist in response to addressing poverty alleviation and vulnerability in Malawi and Zambia. Also, to explore various policies and practices that can be implemented to foster societal resilience to emerging shocks, particularly those of climate change and Covid-19. The study established that in both countries, safety net programmes have had some positive impact on the vulnerable households, as well as acting as a major source of income, especially for older beneficiaries. Similarly, these programmes have enhanced productivity and food security for smallholder farmers. The study concluded with policies that can be implemented to foster household resilience, to emerging shocks in both countries.